GROWING ENTREPRENEURS IN PGMI STUDENTS IN FACING THE ERA OF THE INDUSTRIAL REVOLUTION 4.0 (CASE STUDY OF PGMI FAI UMMAT STUDENTS IN 2022) - Khairuddin Said; Niswatun Hasanah (Bajang Institute, 2022)
Efforts to foster interest in entrepreneurship among students is one form of the success of various universities in an effort to help the government suppress the movement The high number of the workforce is one of the reasons the government continues to make entrepreneurship programs for the community, especially among students. This is certainly a motivation for students to be able to find their potential in creating and innovating in reading business opportunities, so that when graduates are busy looking for work they can create competitive jobs. In this study, the method used is a case study method. This study uses descriptive analysis by conducting direct interviews. Programs that can be carried out to foster student entrepreneurship interest in facing the era of the industrial revolution 4.0 in the PGMI study program include achieving learning outcomes in the curriculum related to entrepreneurship, participating in the Student Creativity Program (PKM) and industrial visits, students participating in every activity related to development. knowledge about entrepreneurship such as attending the National Entrepreneurship Seminar, participants in the Entrepreneurship Public Lecture and participating in various entrepreneurship trainings.